Πορτραίτα - Βασιλικός, Βασίλης, 1934- (Βιβλιοπωλείον της "Εστίας"-Ι.Δ.Κολλάρου, 1976)
Κώστας Γαβράς -- Ουμπέρτο Έκκο -- Μίκης Θεοδωράκης -- Ελία Καζάν -- Ίταλο Καλβίνο -- Αλμπέρ Καμύ -- Μιχάλης Κακογιάννης -- Ελένη Καζαντζάκη -- Τζιόρτζιο ντε Κίρικο -- Μενέλαος Λουντέμης κ.ά.